Social Service Model For Women Ex-Migrant Workers - Maksud Hakim (IHSA Institute, 2022)
Women former migrant workers experience various problems such as discrimination, stigmatization, difficulties with economic resources. Their existence requires assistance in the form of social services organized by the government and other institutions. The main article aims to provide an overview of services that can be carried out to overcome various problems of women ex-migrant workers. This article uses a literature study method to comprehensively describe the services provided. The results of the study show that the social services include assessment, implementation, evaluation and termination. In each stage, it applies gender sensitive values, namely practical needs and strategic needs.